2010
DOI: 10.1093/jat/34.8.430
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Validity of Gas Chromatography-Mass Spectrometry and Liquid Chromatography-Tandem Mass Spectrometry Analysis of Urine Samples II: Amphetamine, Methamphetamine, ( )-3,4-Methylenedioxyamphetamine, ( )-3,4-Methylenedioxymethamphetamine, ( )-3,4-Methylenedioxyethylamphetamine, Phencyclidine, and ( )-11-nor-9-Carboxy- 9-tetrahydrocannabinol

Abstract: On November 25, 2008, the U.S. Department of Health and Human Services posted a final notice in the Federal Register authorizing the use of liquid chromatography-tandem mass spectrometry (LC-MS-MS) and other technologies in federally regulated workplace drug testing (WPDT) programs. To support this change, it is essential to explicitly demonstrate that LC-MS-MS, as a technology, can produce results at least as valid as gas chromatography (GC)-MS, the long-accepted standard in confirmatory analytical technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, the Ki values of ondansetron for MATE1 (0.035 μM) and MATE2-K (0.015 μM) were much lower than that for OCT2 (3.85 μM), by 109 and by 256 folds respectively, indicating that ondansetron is a much potent inhibitor for the formers than the latter. The plasma peak concentrations of ondansetron in patients has been reported to range from 0.10 to 0.42 μM from doses of 8 mg to 32 mg daily (Stout et al, 2010). A Ki value of at least more than one-tenth of C max has been suggested for the drug to cause a clinically recognizable interaction with another drug that is transported by the same transporter (Fenner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Ki values of ondansetron for MATE1 (0.035 μM) and MATE2-K (0.015 μM) were much lower than that for OCT2 (3.85 μM), by 109 and by 256 folds respectively, indicating that ondansetron is a much potent inhibitor for the formers than the latter. The plasma peak concentrations of ondansetron in patients has been reported to range from 0.10 to 0.42 μM from doses of 8 mg to 32 mg daily (Stout et al, 2010). A Ki value of at least more than one-tenth of C max has been suggested for the drug to cause a clinically recognizable interaction with another drug that is transported by the same transporter (Fenner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…analyzed identical samples by using GC/MS and LC/MS/MS and compared the obtained results. LC/MS/MS provided the same accuracy, precision, and specificity in detecting amphetamine (AMP)‐like drugs, morphine (MOR), codeine (COD), 6‐acetylmorphine, and benzoylecgonine as GC/MS did …”
mentioning
confidence: 99%
“…However, ondansetron has a larger inhibitory potency against MATEs as compared with OCTs (Tzvetkov et al, 2012;Li et al, 2013). It has been reported that the peak plasma concentrations of ondansetron in patients range from 0.10 to 0.42 mM from the dose of 8 mg to 32 mg daily (Stout et al, 2010). A K i value of at least more than one-tenth of C max has been considered for the drug to cause a clinically relevant interaction with another drug that is a substrate of the same transporter (Fenner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%